Measuring air-sea gas exchange velocities in a large scale annular wind-wave tank - Mesarchaki, Evridiki; Kräuter, Christine; Krall, Kerstin Ellen; Bopp, Maximilian; Helleis, Frank; Williams, Jonathan M. J.; Jähne, Bernd (Ocean science discussions, 2014)
In this study we present gas exchange measurements conducted in a large - scale wind-wave tank. Fourteen chemical species spanning a wide range of - solubility (dimensionless solubility, α = 0.4 to 5470) and - diffusivity (Schmidt number in water, Scw = 594 to 1194) were - examined under various turbulent (u10 = 0.8 to 15 m - s-1 conditions. Additional experiments were performed under - different surfactant modulated (two different concentration levels of - Triton X-100) surface states. This paper details the complete - methodology, experimental procedure and instrumentation used to derive - the total transfer velocity for all examined tracers. The results - presented here demonstrate the efficacy of the proposed method, and the - derived gas exchange velocities are shown to be comparable to previous - investigations. The gas transfer behaviour is exemplified by contrasting - two species at the two solubility extremes, namely nitrous oxide - (N2O) and methanol (CH3OH). Interestingly, a - strong transfer velocity reduction (up to a factor of three) was - observed for N2O under a surfactant covered water surface. In - contrast, the surfactant affected CH3OH, the high solubility - tracer only weakly.
Gesehen am 21.01.2021